Trade policy issues and empirical analysis - Baldwin, Robert E. (Conference report (National Bureau of Economic Research), 1988)
Interest in U.S. trade policy has been stimulated in recent years by the massive American trade deficit, by the belief that intervention by foreign governments in international markets has given other countries a competitive edge over the United States, and by concern about the increase in protectionism among industrial countries. In turn, major analytical developments in international economics have revolutionized trade theory, broadening its scope both by introducing in a more formal manner such concepts as imperfect competition, increasing returns, product differentiation, and learning effe.